2020
DOI: 10.1007/s13205-020-02487-9
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as key regulators via targeting the phytohormone signaling pathways during somatic embryogenesis of plants

Abstract: Somatic embryogenesis is the regeneration of embryos from the somatic cell via dedifferentiation and redifferentiation without the occurrence of fertilization. A complex network of genes regulates the somatic embryogenesis process. Especially, microRNAs (miRNAs) have emerged as key regulators by affecting phytohormone biosynthesis, transport and signal transduction pathways. miRNAs are small, non-coding small RNA regulatory molecules involved in various developmental processes including somatic embryogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 106 publications
1
8
0
3
Order By: Relevance
“…Polyamines are considered to be a class of compounds related to cellular proliferation (Bais and Ravishankar, 2002;Jimenez, 2005) and play an important role in the regulation of SE (Silveira et al, 2004;Jin et al, 2020;Sundararajan et al, 2021). Moreover, polyamines (PAs) could be associated with the stress caused in plant cells, protecting them and upregulating stress-related genes (Alcazar et al, 2020;Kielkowska and Adamus, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are considered to be a class of compounds related to cellular proliferation (Bais and Ravishankar, 2002;Jimenez, 2005) and play an important role in the regulation of SE (Silveira et al, 2004;Jin et al, 2020;Sundararajan et al, 2021). Moreover, polyamines (PAs) could be associated with the stress caused in plant cells, protecting them and upregulating stress-related genes (Alcazar et al, 2020;Kielkowska and Adamus, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that miR390 stimulates the production of tasiARFs, which repress the expression of their targets ARF3 and ARF4. There was also positive and negative feedback between ARF2/ARF3/ARF4 and miR390 to regulate lateral root growth [ 54 ]. Two highly expressed miRNAs were selected from the ethylene and auxin pathways, and their target genes were verified.…”
Section: Discussionmentioning
confidence: 99%
“…Przeprowadzone analizy polegają głównie na porównaniu zmian w akumulacji miRNA oraz ekspresji genów w kalusie embriogenicznym i nieembriogenicznym lub na różnych etapach SE. Wykorzystując sekwencjonowanie nowej generacji, hybrydyzację northern, analizę bibliotek małych RNA czy mikromacierze, zidentyfikowano aktywność wielu konserwowanych ewolucyjnie rodzin genów MIRNA, charakteryzujących się zmiennym, tkankowo-specyficznym poziomem ekspresji na różnych etapach rozwoju zarodka i wykazano, że miRNA mają wpływ na indukcję SE [109]. Ich kluczową rolę potwierdzono wykorzystując mutanty w genie DICER-LIKE 1, kodującym enzym odpowiedzialny za biosyntezę większości roślinnych miRNA, które to okazały się być niezdolne do formowania somatycznych zarodków na zarodkach zygotycznych standardowo używanych w tym celu u rzodkiewnika [110].…”
Section: Mirnaunclassified